(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The present study aimed that evaluation of anti hyperlipidemic activity of Momordica charantia, stem and root of Tinospora cordifolia, whole plant of Andrographis paniculata and wood of Pterocarpus marsupium and leaves of Gymnema sylvestre by Maceruation method. Individually and combined both plants extracted poly herbal extraction and screened for phytochemical study and Anti-Hyperlidemic activity by Triton X 100 Induced Hyperlipidemia model, High Fat Diet (FD) induced hyperlipidemic model, Estimation of Serum total cholesterol (TC) CHOD- PAP, Estimation of serum triglycerides, Estimation of HDL-cholesterol, Estimation of LDL cholesterol, Phytochemical investigation reveals the presence of alkaloids, flavonoids, saponins, tannins, steroids, triterpinoids, carbohydrates and glycosides in poly herbal methanolic extraction and individual plant extraction, In acute toxicity studies no mortality was observed with either of the extracts even at the dose level of 2000 mg/kg body weight In the present study, the methanol extracts of three plants reduced the cholesterol and triglycerides in a manner similar to the reduction facilitated by atorvastatin. The hypolipidemic activities of atorvastatin and the methanol extract of individual and polyherbal extraction were evident in both synthesis and excretory phases of triton-induced hyperlipidemia in rats.